2021
DOI: 10.1038/s41598-021-95618-y
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic nsSNPs that increase the risks of cancers among the Orang Asli and Malays

Abstract: Single-nucleotide polymorphisms (SNPs) are the most common genetic variations for various complex human diseases, including cancers. Genome-wide association studies (GWAS) have identified numerous SNPs that increase cancer risks, such as breast cancer, colorectal cancer, and leukemia. These SNPs were cataloged for scientific use. However, GWAS are often conducted on certain populations in which the Orang Asli and Malays were not included. Therefore, we have developed a bioinformatic pipeline to mine the whole-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 119 publications
0
7
0
Order By: Relevance
“…The association of rs1393350 and AK risk reached a genome-wide level of significance in our study, and we identified an additional lead SNP rs1126809 at the TYR locus. SNP rs1126809 has been associated with a low tan response and increased risk of keratinocyte carcinomas and melanoma 16 , 18 , 24 , 25 , 31 , and it may cause changes at the post-translational modification site, leading to dysregulation of melanin synthesis within the melanosomes 32 . Similarly, SNP rs16891982 lies in SLC45A2 , which encodes a transporter protein that mediates melanin synthesis, correlates with reduced melanin content in cultured human melanocytes 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The association of rs1393350 and AK risk reached a genome-wide level of significance in our study, and we identified an additional lead SNP rs1126809 at the TYR locus. SNP rs1126809 has been associated with a low tan response and increased risk of keratinocyte carcinomas and melanoma 16 , 18 , 24 , 25 , 31 , and it may cause changes at the post-translational modification site, leading to dysregulation of melanin synthesis within the melanosomes 32 . Similarly, SNP rs16891982 lies in SLC45A2 , which encodes a transporter protein that mediates melanin synthesis, correlates with reduced melanin content in cultured human melanocytes 33 .…”
Section: Discussionmentioning
confidence: 99%
“…4,12,13 They can alter protein functions by inactivating active sites of enzymes, deflecting the folding patterns, changing the solubility and stability, and so on. [14][15][16][17] Moreover, nsSNPs have a significant impact on the functional diversity of coded proteins and are found to promote pathogenesis in various types of cancer, 18,19 sickle-cell anemia, 20 β-thalassemia, 21 cystic fibrosis, 22 Alzheimer's disease, and so forth. 23 Gastric cancer (GC), commonly known as stomach cancer, continues to be one of the deadliest types of cancer in the world, with the third-highest lethality and the fourth-highest morbidity rate.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 12 , 13 They can alter protein functions by inactivating active sites of enzymes, deflecting the folding patterns, changing the solubility and stability, and so on. 14 , 15 , 16 , 17 Moreover, nsSNPs have a significant impact on the functional diversity of coded proteins and are found to promote pathogenesis in various types of cancer, 18 , 19 sickle‐cell anemia, 20 β‐thalassemia, 21 cystic fibrosis, 22 Alzheimer's disease, and so forth. 23 …”
Section: Introductionmentioning
confidence: 99%
“…The non-synonymous single-nucleotide polymorphisms (nsSNPs) in proteins perturb their structure and function. nsSNPs are single-base changes leading to a change in the amino acid sequence of the encoded protein, and several of these variants are associated with disease [ 13 , 14 ]. These nsSNPs can affect important biological pathways by disrupting protein–protein interaction [ 15 ], inducing changes in protein conformation [ 16 ], or affecting the post-translational modification sites [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…nsSNP mutations in oncoproteins are frequently observed in cancer, and an attempt to restore their functionality is a recent therapeutic strategy. Recent studies revealed that the utilization of in silico approaches for evaluating protein–protein interactions and analyzing SNPs provided evidence that mutations are associated with various disease conditions [ 13 , 14 , 21 ].…”
Section: Introductionmentioning
confidence: 99%